2021
DOI: 10.1038/s41598-021-87926-0
|View full text |Cite|
|
Sign up to set email alerts
|

Ambulatory cataract surgery centre without perioperative anaesthesia care: a prospective cohort study

Abstract: This study aims to evaluate the safety and patient satisfaction of a fast-track procedure for cataract surgery under topical anaesthesia without perioperative anaesthesia care. This is a prospective single-centre study including all cataract procedures in the Centre Ambulatoire de la Chirurgie de la Cataracte at the Hospital of Bourges between May and August 2018. Procedures were performed under topical anaesthesia without the presence of a nurse anaesthesiologist or anaesthesiologist, the patient had not fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Due to recent technological advances and improvements in the safety of the procedure, most surgeries are now performed using topical anesthesia with eye drops; therefore, anesthesiologists are rarely required during the procedure. Murray et al [5] reported only one serious adverse event in a series of 6661 cataract surgeries and concluded that most cataract surgery procedures under local anesthesia could be safely performed without the presence of an anesthesiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Due to recent technological advances and improvements in the safety of the procedure, most surgeries are now performed using topical anesthesia with eye drops; therefore, anesthesiologists are rarely required during the procedure. Murray et al [5] reported only one serious adverse event in a series of 6661 cataract surgeries and concluded that most cataract surgery procedures under local anesthesia could be safely performed without the presence of an anesthesiologist.…”
Section: Discussionmentioning
confidence: 99%
“…Several international ophthalmic and nonophthalmic societies have encouraged abandoning or limiting low-value care. 3,4 Among them is the Finnish Medical Society, whose current care guidelines for treatment of adult cataracts 5 justifies the use of general anesthesia in exceptional cases only. These guidelines and the evidence from administrative support systems should inform clinical decision-making and aid in the conversion of practices in the local units.…”
Section: Perioperative Risk Assessment and Avoiding Overuse Of Anesth...mentioning
confidence: 99%
“…1 Drs Nemet and Tuuminen's experiences in Finland add to the growing body of literature suggesting that complications after cataract surgery are exceedingly rare, even though anesthesia care for cataract surgery is used much more selectively at their institution than it is in the US. This approach to cataract surgery sedation is also the prevailing practice throughout the UK, 2 as well as at other dedicated eye care centers, 3,4 and has been shown to be safe and acceptable to patients in these settings.…”
Section: Achia Nemet MD Raimo Tuuminen Md Phdmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example of the spectrum of ambulatory interventions, older patients undergoing cataract surgery often present with significant comorbidities [11 ▪ ]. Still, this surgery can be safely performed in most patients by implementing topical or regional anesthesia, even without preoperative anesthesiologic evaluation [6 ▪ ]. Likewise, even major surgeries such as colectomies can be handled on an ambulatory basis after careful patient selection [12].…”
Section: Why Do We Assess Risk – Who Needs What?mentioning
confidence: 99%